Amazonian Dark Earths in Bolivia? A soil study of anthropogenic ring ditches near Baures (eastern Llanos de Mojos) - Hastik, Richard; Geitner, Clemens; Neuburger, Martina (ERDKUNDE, 2013)
Archaeological, pedological and ethnobotanical research of the last decades brought new insights on the view on human-environment interrelations in the Amazon. In this context, we analyse possible links between Amazonian Dark Earths (Terra Preta do Índio) traditionally known from the central Amazon of Brazil and pre-Colombian Earthworks (ring ditches) in the Llanos de Mojos of Bolivia. By doing so, we also discuss the local inhabitants’ perception of soils and scrutinise the importance of soil fertility. Therefore, various methods such as interviews, field surveys, soil profile discussions and laboratory analyses were applied. Results show that soils tend to have particular characteristics at ring ditches in contrast to surrounding areas. The combination of distinctively elevated phosphorus values, darker soil colour and the occurrence of potsherds indicate the presence of the Amazonian Dark Earth type “Terra Mulata” at ring ditch sites. Interviews reveal that local farmers are aware of the increased soil fertility of “Tierras Negras” within ring ditches. Nevertheless, incentives for using those soils are low due to the limited land use pressure and generally more favourable reference soils in contrast to central Amazonian Ferralsols. We finally discuss integrative approaches covering aspects of both physical and social science as pursued within the presented work in context of the dichotomy between human and physical geography.